APLIKASI LAYANAN PENGADUAN PELANGGARAN SISWA PADA SMA NEGERI 7 KOTA JAMBI: Applications, Services Complaints violation of the student, web technology, library - Limia Budiarti, Rike; Perdana Putra, Nanda (JURNAL AKADEMIKA, 2019)
Application is a computer program made to do and carry out special tasks from the user, where the application can be used to facilitate a lot of people in their daily activities. At SMA Negeri 7 jambi City, the scope of supervision regarding the violation of students is still relatively small, it is impossible because the student staff to constantly monitor the students inside and outside the school continuously. if applied constant supervision, it would take a very large cost. Having Applied this application then allows the csommunity to assist in supervising the students outside the school.